Olfaction in Neuropathologically Defined Progressive Supranuclear Palsy. Issue 7 (23rd March 2021) - Shill, Holly A.; Zhang, Nan; Driver‐Dunckley, Erika; Mehta, Shyamal; Adler, Charles H.; Beach, Thomas G.
Abstract: Background: Hyposmia is characteristic of idiopathic Parkinson's disease (PD) and dementia with Lewy bodies (DLBs), whereas progressive supranuclear palsy (PSP) typically has normal sense of smell. However, there is a lack of pathologically confirmed data. Objective: The objective is to study hyposmia in pathologically confirmed PSP patients and compare to PD patients and nondegenerative controls. Methods: We studied autopsied subjects in the Arizona Study of Aging and Neurodegenerative Disorders who had antemortem olfactory testing and a neuropathological diagnosis of either PD, PSP, or control. Results: This study included 281 cases. Those with neuropathologically confirmed PSP (N = 24) and controls (N = 174) had significantly better sense of smell than those with PD (N = 76). Although most PSP patients had normal olfaction, there were some with hyposmia, resulting in an overall reduced sense of smell in PSP compared to controls. The sensitivity of having PSP pathologically in those presenting with parkinsonism and normosmia was 93.4% with a specificity of 64.7%. Cases with both PSP and PD pathologically had reduced sense of smell similar to PD alone (N = 7). Hyposmic PSP patients had significantly higher Lewy body burden not meeting criteria for additional PD/DLB diagnosis. Conclusions: Pathologically confirmed PD had reduced olfaction compared with PSP or controls. In the setting of parkinsonism in this sample, the presence of normosmia had high sensitivity for PSP. Hyposmia in PSP suggests the presence of additional Lewy body pathology. © 2021 International Parkinson and Movement Disorder Society